(untitled) (KONFERENSIYA, 2025)
Modern technology has significantly reshaped foreign language learning by providing learners with new ways to communicate, interact, and study independently. This article explores how tools such as multimedia resources, mobile apps, online video libraries, and virtual classrooms support the development of all language skills through authentic and interactive activities. It also emphasizes the need for teachers’ digital competence. Overall, technology has become a key element in effective language acquisition, not just a supplementary tool.